Climate Justice in Maqashid Shariah, Contemporary Fiqh and Common Responsibility Principle - Nurjanah Nurjanah; Hifdhotul Munawaroh (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2025)
Climate change is one of the most urgent global challenges, raising fundamental questions about justice, responsibility, and moral obligation. This study examines climate justice through two intersecting frameworks: the principle of Common but Differentiated Responsibilities in international law and the values of maqashid al-shariah and contemporary fiqh in Islamic jurisprudence. Using a normative-doctrinal method with comparative and conceptual approaches, the research analyzes international instruments such as the United Nations Framework Convention on Climate Change, the Kyoto Protocol, and the Paris Agreement alongside classical and modern Islamic legal thought. The findings show that while the principle of differentiated responsibilities provides a sound normative basis, its implementation remains weak due to geopolitical imbalances and the absence of binding enforcement mechanisms. In contrast, maqashid al-shariah—particularly the protection of life, lineage, wealth, intellect, and religion—offers a comprehensive moral-spiritual framework that reinforces differentiated responsibilities. Both frameworks converge on principles of capacity-based responsibility, intergenerational justice, the no-harm rule, and global solidarity. The study proposes a Maqashid-Based Integrative Climate Justice Model consisting of three pillars: value-grounded differentiated responsibility, expanded subjects of responsibility beyond states, and an equitable mechanism for loss and damage, contributing to stronger international climate governance.